2020
DOI: 10.1101/2020.02.17.952754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Branched chain amino acid aminotransferase 2 Regulates Ferroptotic Cell Death in Cancer Cells

Abstract: i contribute equally to this manuscript. Conflict of interest statementThe authors have declared that no conflict of interest exists. AbstractFerroptosis has been implicated as a tumor-suppressor function for cancer therapy.Recently the sensitivity to ferroptosis was tightly linked to numerous biological processes, including metabolism of amino acid. Here, using a high-throughput CRISPR/Cas9 based genetic screen in HepG2 cells to search for metabolic proteins inhibiting ferroptosis, we identified branched chai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Lipid Peroxidation Assay. The relative MDA level in cells or tumor issues lysates was measured using a Lipid Peroxidation (MDA) Assay Kit (Abcam, ab118970), and the experiments were carried out as described previously [12]. Cells or tumor tissues were homogenized with lysis buffer and the MDA in samples reacts with thiobarbituric acid (TBA) to generate an MDA-TBA adduct which can be quantified colorimetrically (OD = 532 nm).…”
Section: Cell Viability Assay Cell Viability Was Measured Usingmentioning
confidence: 99%
“…Lipid Peroxidation Assay. The relative MDA level in cells or tumor issues lysates was measured using a Lipid Peroxidation (MDA) Assay Kit (Abcam, ab118970), and the experiments were carried out as described previously [12]. Cells or tumor tissues were homogenized with lysis buffer and the MDA in samples reacts with thiobarbituric acid (TBA) to generate an MDA-TBA adduct which can be quantified colorimetrically (OD = 532 nm).…”
Section: Cell Viability Assay Cell Viability Was Measured Usingmentioning
confidence: 99%
“…Furthermore, another study also identified BCAT2 as a novel suppressor of ferroptosis, whose activation of ectopic expression could specifically antagonize system Xcinhibition and protect liver cancer and pancreatic cancer cells from ferroptosis. Therefore, BCAT2 could serve to predict the responsiveness of cancer cells to the ferroptosisinducing therapy [104]. Together, reprogramming of BCAA metabolism could change mitochondrial functions as well as gene expression, redraw other metabolic pathways, and change the levels of essential metabolites, including Glu, α-KG, BCAAs and ROS, therefore elevating cancer cell proliferation and enhancing drug resistance capacity [98].…”
Section: Branched-chain Amino Acids Metabolismmentioning
confidence: 99%
“…Intracellular ferrous iron level was determined using the iron assay kit (Abcam, ab83366) according to the manufacturer's instructions [38].…”
Section: Iron (Fe2+) Assaymentioning
confidence: 99%